Analysis of the Needs of SiCerMa (Human Digestive System) Interactive Media Based on Problem Based Learning in Grade V Elementary School Students - Ria Juhariyani; Sarwanto; Roemintoyo (Didaktika: Jurnal Kependidikan, 2026)
The lack of optimal use of learning media in the classroom is one of the factors causing the low science learning outcomes of grade V elementary school students, especially the material of the human digestive system. The purpose of this study is to analyze the needs of SiCerMa media as a support for learning material on the human digestive system. The subjects of this study are 30 students and 30 teachers. The method used is quantitative with ADDIE's development model focusing on needs analysis. The data collection technique is by distributing questionnaires. The data analysis technique uses analysis from Milles Huberman. The results of the study showed that 93% of the student needs analysis questionnaire was obtained while 90% of teachers said that they needed PBL-based Si CerMa interactive media to improve the science learning outcomes of grade V elementary school students. In conclusion, information was obtained that teachers and students alike need concrete learning media that are interesting and interactive to help facilitate the understanding of the material of the human digestive system.